Análisis psicométrico de la escala de cansancio emocional en estudiantes de una universidad privada - Dominguez Lara, Sergio Alexis (2014)
The aim of this instrumental study was to analyze the psychometric properties of the Emotional Exhaustion Scale (EES) in a sample of 233 private university students of psychology with ages between of 16 and 44 years old (M = 20.9). The factor analysis reveals that the EES presents a one-dimensional structure (a factor that explains 43.361% of the total variance) and there was a significant and positive correlation between anxiety and depression and a significant and negative correlation with Academic Self-Efficacy. Furthermore, regarding reliability, the ordinal alpha is adequate (.853). To conclude, the EAPESA has suitable psychometric properties to continue validation studies, which reaffirms its use as an instrument to evaluate emotional exhaustion.